Pertimbangan Hukum Majelis Pengawas Daerah (MPD) Kota Palangka Raya dengan Majelis Pengawas Wilayah (MPW) Provinsi Kalimantan Tengah dalam Memutuskan suatu Perkara di Wilayah Kalimantan Tengah - Reinaldo, Ivan Nico (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
The purpose of this study is to determine and examine the authorities to hold and/or conduct examinations of notaries who commit violations, both in the form of the Notary Code of Ethics and provisions in applicable laws and regulations. The first research result: Supervision carried out by the Notary Supervisory Board to prevent violations of the Notary's position is carried out by holding seminars on notary affairs, holding meetings once a month attended by the Regional Supervisory Board to provide direction to implement the UUJN and Code of Ethics and Notaries are required to continue to increase their insight into notary affairs, and the Regional Supervisory Board visits the Notary's office at least once a year to check the Notary's protocol. Second: there is no difference at all between the Notary Supervisory Board and the Notary's Honorary Council because basically preventive supervision is preventive or mitigating so that violations of the Notary Code of Ethics and the Notary's position authority do not occur. Furthermore, regarding the differences in reports from the public addressed to the Notary Supervisory Board and the Notary Honorary Council, there is no difference at all, so if the public reports to one of these organizations, it is possible, but it will be followed up by the authorized organization because it concerns the sanctions that will be given.